Investigating the Impact of Corporate Social Responsibility Disclosure on Firm Financial Performance: Evidence from UK FTSE 250 Companies - WU, QIAN (2020)
Over the past 50 years, the relationship between corporate social responsibility and firm financial performance has been a popular subject for corporate governance, but the research findings always remain inconclusive. This dissertation attempt to analyze the impact of corporate social responsibility (CSR) disclosure on corporate financial performance (CFP) of UK FTSE 250 companies. Environmental, social and governance (ESG) scores are used to measure CSR disclosure, accounting profitability proxied by ROA and ROE and market value proxied by Tobin’s Q and P/E Ratio are used to measure firm financial performance. Data is obtained from Fame and Bloomberg for the years between 2011 and 2019. Multiple regression models, panel data estimators and correlation analysis are employed to examine the CSR-CFP relationship. The empirical results indicate that ESG disclosure has a significantly negative relationship with ROA and ROE. However, it is also found that ESG disclosure has a significantly positive effect on P/E ratio while has a positive but insignificant correlation with Tobin’s Q. Overall, it is concluded that ESG disclosure has a negative effect on accounting profitability and a partial positive effect on market value creation.